2017
DOI: 10.1016/j.athoracsur.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Experience of Coronary Endarterectomy for the Diffusely Diseased Left Anterior Descending Artery

Abstract: CE for a diffusely diseased LAD using the ITA provides satisfactory clinical outcomes with favorable rates of angiographic patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
1
29
1
3
Order By: Relevance
“…In Nishigawa et al [20] study conventional angiography was done at a median of 7 days (range 0-85 days) and showed a patency rate of 91.6 percent. Takanashi et al [21] showed early patency of 94 percent.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Nishigawa et al [20] study conventional angiography was done at a median of 7 days (range 0-85 days) and showed a patency rate of 91.6 percent. Takanashi et al [21] showed early patency of 94 percent.…”
Section: Discussionmentioning
confidence: 95%
“…Nishigawa et al [20] reported mortality of 1.1 percent, Schmitto et al [16] 5 percent, Takanashi et al [21] 2.7 percent, Byrne et al [17] 3 percent, Nishi et al [19] 2.9 percent. In comparing LIMA to saphenous group mortality was 4.5 percent in the LIMA group and none in the saphenous group and was not statistically significant.…”
Section: Discussionmentioning
confidence: 97%
“…[11,12] в 1965 г. Данный метод также длительно не использовался в коронарной хирургии ввиду высокой операционной летальности и был возобновлен только 20 лет спустя J. Hitcock и соавт. [13]. В последнее десятилетие в связи с увеличением среднего возраста больных, эффективным медикаментозным лечением ИБС и частым выполнением ЧКВ увеличилось количество пациентов с протяженным и диффузно-дистальным поражением коронарных артерий [14].…”
Section: Discussionunclassified
“…All this could explain the better results of ITA grafts and reassure surgeons about ITA as preferred conduits also in revascularizing symptomatic MCAS [1]. Besides, in multisegmental lesions, typically of the left anterior descending coronary artery, an associated endarterectomy downstream to a MCAS increases the graft run-off, through new-open septal perforator collaterals [4].…”
Section: Surgery Of Moderate Coronary Artery Stenosismentioning
confidence: 99%